2010
DOI: 10.1007/s10856-010-4091-8
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and computational characterization of designed and fabricated 50:50 PLGA porous scaffolds for human trabecular bone applications

Abstract: The present study utilizes image-based computational methods and indirect solid freeform fabrication (SFF) technique to design and fabricate porous scaffolds, and then computationally estimates their elastic modulus and yield stress with experimental validation. 50:50 Poly (lactide-co-glycolide acid) (50:50 PLGA) porous scaffolds were designed using an image-based design technique, fabricated using indirect SFF technique, and characterized using micro-computed tomography (micro-CT) and mechanical testing. Micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
27
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 59 publications
3
27
0
1
Order By: Relevance
“…Also, inadequate control over the porous architecture is evident, and a separate mold for each exterior geometry is required [10,11]. Furthermore, due to the randomly located pore distribution, it is impossible to precisely control pore location, pore diameter, pore interconnectivity, wall thickness, and location [12]. Researchers have demonstrated that by tuning the pore network architecture of a scaffold using rapid prototyping techniques, homogenous cell distribution, sustained nutrient, and oxygen accessibility are achieved [13].…”
Section: Introductionmentioning
confidence: 99%
“…Also, inadequate control over the porous architecture is evident, and a separate mold for each exterior geometry is required [10,11]. Furthermore, due to the randomly located pore distribution, it is impossible to precisely control pore location, pore diameter, pore interconnectivity, wall thickness, and location [12]. Researchers have demonstrated that by tuning the pore network architecture of a scaffold using rapid prototyping techniques, homogenous cell distribution, sustained nutrient, and oxygen accessibility are achieved [13].…”
Section: Introductionmentioning
confidence: 99%
“…These cells and growth factors are housed within scaffolds made of a variety of materials. Polypropylene fumarate, 3,4 poly-e-caprolactone (PCL), [5][6][7] polylactic acid, 8,9 and poly(lactic-co-glycolic) acid 10,11 are bioresorbable polymers that have all been investigated, alone or in combination, for bone applications, as have osteoconductive materials such as tricalcium phosphate, 8 hydroxyl apatite, 12 and calcium phosphate. 13,14 This work employs the use of PCL scaffolds seeded with BMP-7-transduced human gingival fibroblasts to study the effects that permeability has on bone tissue regeneration.…”
mentioning
confidence: 99%
“…18 However, these techniques were not applicable to SFF scaffolds, especially PLLA and PLGA scaffolds, since they are much stiffer than scaffolds fabricated using porogen leaching methods. 16,21 Therefore, to access the cross section of the mineral layers, plastic embedding techniques were utilized and showed the mineral layers covered the inside of the porous scaffolds and also followed the SFF scaffolds architectures. This section technique allowed demonstration of coating on both pre-and postimplanted scaffolds by SEM without losing the scaffold structures.…”
Section: L-ct For Nondestructive Characterization Of Biomineral Coatingsmentioning
confidence: 99%
“…[12][13][14][15] In this system, images are obtained by material attenuation of X-ray to evaluate scaffold geometry and simulate mechanical behavior. 13,14,16 The existence of biomineral coatings on polymer scaffold surfaces also have been examined using m-CT since polymer is almost radio transparent compared to other radio-dense materials. [17][18][19] However, the 3D volume and distribution of mineral coating within porous scaffolds has not been precisely quantified and verified versus destructive methods.…”
mentioning
confidence: 99%